2014
DOI: 10.1371/journal.pone.0114195
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Stimulates Intestinal Epithelial Proliferation and Repair after Injury

Abstract: IL-6 is a pleiotropic cytokine often associated with inflammation. Inhibition of this pathway has led to successful treatment of rheumatoid arthritis, but one unforeseen potential complication of anti-IL-6 therapy is bowel perforation. Within the intestine, IL-6 has been shown to prevent epithelial apoptosis during prolonged inflammation. The role of IL-6 in the intestine during an initial inflammatory insult is unknown. Here, we evaluate the role of IL-6 at the onset of an inflammatory injury. Using two murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(169 citation statements)
references
References 34 publications
6
161
1
1
Order By: Relevance
“…The lack of changes in IL-1β or TNF expression observed in this study is in line with the pleiotropic nature of IL-6, which has both pro-inflammatory and regulatory roles. In this latter context, it promotes intestinal epithelial proliferation and repair [59], and also regulates small intestinal crypt homeostasis [60]. IL-6 has been shown to induce changes in colonic secretory activity and to increase intestinal permeability in the colon [61, 62].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of changes in IL-1β or TNF expression observed in this study is in line with the pleiotropic nature of IL-6, which has both pro-inflammatory and regulatory roles. In this latter context, it promotes intestinal epithelial proliferation and repair [59], and also regulates small intestinal crypt homeostasis [60]. IL-6 has been shown to induce changes in colonic secretory activity and to increase intestinal permeability in the colon [61, 62].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 therefore can have a protective effect and modulator for the immune response (Korolkova et al, 2015). The result of the present study indicated an increase in IL-6 in the acute phase of ulcerative colitis induced by acetic acid intra rectal infusion, this increase could be attributed to the consequence of mucosal T-cell or macrophage activation ( Jones et al, 1994) or IL-6 was induced early after injury in a population of intraepithelial lymphocytes (IELs) induced by acetic acid (Kuhn et al, 2014). Actually, serum IL-6 and IL-8 concentrations are often considered to be reli able markers for CD or UC and correlate with inflammatory activity (Rodriguez et al, 2012) The significant increase in serum IL-6 during the first day of treatment with lactobacillus indicated the great macrophages activation , in accordance with Galdeano and Perdigon (2006) who found when lactobacillus improved the production of IL-6 and antimicrobial activity against S. typhimurium, since activated macrophages produce large amounts of inflammatory cytokines and thus establish a pro-inflammatory environment for other immune cells in the gut (Sanchez-Muñoz et al, 2008).…”
Section: Serum Leptin and Il-6mentioning
confidence: 52%
“…16,17 Some studies also indicated that IL-6 and IL-8 are two of major human cytokines that were rapidly induced in intestinal epithelial cells synergistically with IL-1 or TNFalpha after mucosal injury, inflammation, or stimulation for repairing damaged mucosa. 18,19 Colonoscopy with biopsy or polypectomy is associated with increased risk of mucosal injury and complications. 20,21 Therefore, colonoscopy with therapeutic procedures itself may increase IL-6 and IL-8 and contribute to the pathophysiology of CP/CPPS.…”
Section: Discussionmentioning
confidence: 99%
“…We first excluded all subjects who had a history of CP/CPPS since the beginning of the NHI program in 1995. Thereafter, we selected 3933 controls matched with cases by age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)30-39, 40-49, 50-59, 60-69, and >69 years) and index year. We selected the controls by matching them to a given CP/CPPS case simply due to use of medical services in the same index year of that particular case.…”
Section: Selection Of Cases and Controlsmentioning
confidence: 99%